Description of the F-0 larvae of Brechmorhoga latialata González-Soriano, 1999 and B. tepeaca Calvert, 1908 (Odonata: Libellulidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio (Zootaxa, 2025)
The last instar larvae of Brechmorhoga latialata González-Soriano, 1999 and B. tepeaca Calvert, 1908 are described and illustrated in detail based on reared larvae. Both are diagnosed and compared with the larvae of other species of Brechmorhoga Kirby described to date. The main structural features that distinguish the larva of B. latialata from that of B. tepeaca are the number of setae on palp and prementum, the shape of the ligula, the palp crenations, the ventral margin of propleura, the size of abdominal dorsal protuberances, and the length of posterolateral spines on S8–9 and caudal appendages.